Deformation and fracture mechanics of engineering materials - Hertzberg, Richard W. , 1937-; Hertzberg, Jason L. , 1969-; Vinci, Richard Paul (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"Hertzberg's 5th edition of Deformation & Fracture Mechanics of Engineering Materials offers several new features including a greater number and variety of homework problems using more computational software; more "real world" applications of theories, case studies; and less coverage of metals. Furthermore, this edition has more focus shifted toward emerging technologies (nanotechnology, micro mechanical systems), dislocations, macroscale plasticity; nanomaterials, biomaterials, smart materials and a new chapter on products liability/recall - supported by vast majority of survey respondents"-
1. Elastic response of solids -- 2. Yielding and plastic flow -- 3. Controlling strength -- 4. Time-dependent deformation -- 5. Fracture: an overview -- 6. Elements of fracture mechanics -- 7. Fracture toughness -- 8. Environment-assisted cracking -- 9. Cyclic stress and strain fatigue -- 10. Fatigue crack propagation -- 11. Analyses of engineering failures -- 12. Consequences of product failure
Includes bibliographical references and index
Keywords: Deformations (Mechanics); Fracture mechanics